Transaction Costs and Interest Arbitrage: Tranquil versus Turbulent Periods - Frenkel, Jacob A.; Levich, Richard M. (Journal of Political Economy, 1977)
This paper deals with the effects of transaction costs on the efficacy of covered interest arbitrage during three periods: 1962-67, the tranquil peg; 1968-69, the turbulent peg; and 1973-75, the managed float. Several conclusions emerge: (i) during the managed float transaction costs have risen dramatically, (ii) these costs played a similar role in accounting for deviations from parity during the periods of the tranquil peg and the managed float but not during the turbulent peg. Similar conclusions emerge from a time-series analysis of the various exchange rates with the implication that a classification of periods according to the degree of turbulence is preferred to a classification based on the legal arrangement (e.g., pegged or floating rates), and (iii) covered interest arbitrage does not seem to entail unexploited opportunities for profits.